2019
DOI: 10.1021/acs.analchem.9b03935
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Encoded Polystyrene Microbeads as a Mass Cytometry Calibration/Normalization Standard Covering Channels from Yttrium (89 amu) to Bismuth (209 amu)

Abstract: Mass cytometry (MC) measures metal isotope signals from single cells and bead samples. Since large numbers of isotopes can be employed as labels, mass cytometry is a powerful analytical technique for multiparameter cytometric assays. The calibration protocol in MC is a critical algorithm, which employs metal-encoded microbeads as an internal standard to correct the data for instrumental signal drift. The current generation of commercially available beads carries four lanthanide elements (cerium, europium, holm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 26 publications
1
32
0
Order By: Relevance
“…further improved the isotopic range of EQ 4 beads by adding 3 elements ( 89 Y, 115 In, and 209 Bi), resulting in a total of 7 isotopes. The authors demonstrated that the EQ4 beads did not consistently normalize isotope signals outside the mass range of 140-175, whereas the 7-element calibration bead system resolved this issue ( 175 ). As of the time of this manuscript publication, 7-element beads are not available for purchase and interested parties must synthesize these themselves.…”
Section: Sample Acquisition and Data Outputmentioning
confidence: 99%
“…further improved the isotopic range of EQ 4 beads by adding 3 elements ( 89 Y, 115 In, and 209 Bi), resulting in a total of 7 isotopes. The authors demonstrated that the EQ4 beads did not consistently normalize isotope signals outside the mass range of 140-175, whereas the 7-element calibration bead system resolved this issue ( 175 ). As of the time of this manuscript publication, 7-element beads are not available for purchase and interested parties must synthesize these themselves.…”
Section: Sample Acquisition and Data Outputmentioning
confidence: 99%
“…(3) They have a very small bead-to-bead variation in the metal ion content . So far, the main application of polystyrene particles is as internal standards for cell studies. ,, Metal-containing polystyrene beads consist of a mixture of known isotopes to cover the mass cytometer range of detection. Initially, a set of calibration beads containing five lanthanide isotopes ( 139 La, 141 Pr, 159 Tb, 169 Tm, and 175 Lu) were synthesized (by DVS Sciences, now Fluidigm Canada).…”
Section: Mass-tag Reagentsmentioning
confidence: 99%
“…Nonetheless, the newest mass cytometry instrument, Helios, covers a range of detection from 89 Y to 209 Bi. The expansion in the number of channels that can be detected in mass cytometry makes it necessary to include new metals within the standard metal-encoded particles to cover the ranges of 89 Y– 140 Ce and 175 Lu– 209 Bi . We expect that these polystyrene particles containing seven elements as standards will be the next generation of calibration beads in mass cytometry given that they cover a range of masses that are inaccessible with the current generation of calibration beads.…”
Section: Mass-tag Reagentsmentioning
confidence: 99%
“…Our results showed lanthanide ions with smaller ionic radii (e.g., Ho 3+ and Lu 3+ ) tend to be incorporated into microbeads much more efficiently than lanthanide ions with larger ionic radii (e.g., Ce 3+ and Eu 3+ ). 14,15 As a consequence, we had to carry out many attempts to formulate the lanthanide feed in the bead synthesis to obtain a batch of microbeads with the desired encoded lanthanide content. This lack of controllability is a time-consuming problem, when one seeks to synthesize a library of microbeads encoded with various metal ions and defined metal content at different levels for each metal.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Bi atoms/bead, were the same samples as described in our previous publication. 15 EQ Four Element (eq 4) Calibration Beads for MC were kindly provided by Fluidigm Canada. Deionized water was produced by a Millipore purification system with a minimum resistivity of 18 MΩ cm.…”
Section: ■ Introductionmentioning
confidence: 99%